Exploring theological perspectives on adult social care. Issue 3 (May 2022) - Rand, Stacey
A number of theological perspectives on adult social care are considered to illustrate how theology can be brought into creative dialogue with the practical and ethical issues in a way that may inform the ongoing public debate.